Meson phenomenology and phase transitions in nonlocal chiral quark models - Carlomagno, Juan Pablo (2015)
We study the features of nonlocal chiral quark models that include wave function renormalization. Model parameters are determined from meson phenomenology, considering different nonlocal form factor shapes. In this context we analyze the characteristics of the deconfinement and chiral restoration transitions at finite temperature and chemical potential, introducing the couplings of fermions to the Polyakov loop for different Polyakov potentials. The results for various thermodynamical quantities are compared with data obtained from lattice QCD calculations.